Physical properties of different cultivar local glutinous rice (Susu and Siding) and commercial Thai cultivar - Zainal, Norzahirah; Shamsudin, Rosnah (HH Publisher, 2021)
Glutinous rice (Oryza sativa var. glutinosa) is known as waxy rice or sticky rice and it has an opaque and small size grain cultivar distinct from common white rice. In outlining the equipment for processing, storage, sorting, sizing and other post-harvest equipment, the physical properties are very important. Two different cultivars of Malaysian local glutinous rice known as Susu and Siding were evaluated in this study. The objective of this study is to compare the physical properties of two different local cultivars in designing the rice processing equipment. For Susu cultivar, the average of length, width and thickness were 6.63 mm, 1.88 mm and 1.50 mm, respectively. The corresponding values were 6.24 mm, 1.98 mm and 1.48 mm for Siding cultivar. For Susu cultivar, the average of aspect ratio, sphericity, volume, surface area, bulk density, true density, porosity, 1000 weight kernel and angle of repose were 0.28, 0.40%, 9.81 mm3, 19.02 mm2, 800.54 kg/m3, 1500.36 kg/m3, 46.65%, 18.88 g and 39.45°, respectively. The corresponding values were 0.32, 0.42%, 10.25 mm3, 19.45 mm2, 772.73 kg/m3, 1229.51 kg/m3, 37.15%, 17.04 g and 40.08° for Siding cultivar. The physical properties of the same cultivar (Susu) showed no significant difference, but apparently Siding was higher in bulk density, which requires a larger-sized silo compared to Susu cultivar in term of equipment design.